Overexpression of MsSAG113 gene promotes leaf senescence in alfalfa via participating in the hormone regulatory network - Li, Shuwen; Xie, Hong; Zhou, Lingfang; Dong, Di; Liu, Yaling; Jia, Chenyan; Han, Liebao; Chao, Yuehui; Chen, Yinglong (Frontiers in Plant Science, 2022)
Alfalfa (Medicago sativa) is a kind of high quality leguminous forage species, which was widely cultivated in the world. Leaf senescence is an essential process in plant development and life cycle. Here, we reported the isolation and functional analysis of an alfalfa SENESCENCE-ASSOCIATED GENE113 (MsSAG113), which belongs to the PP2C family and mainly plays a role in promoting plant senescence. The MsSAG113 gene was isolated from alfalfa, and the transgenic plants were obtained by Agrobacterium-mediated method. Compared with the wildtype, transgenic plants showed premature senescence in leaves, especially when cultivated under dark conditions. Meanwhile, application of exogenous hormones ABA, SA, MeJA, obviously acclerated leaf senescence of transgenic plants. Furthermore, the detached leaves from transgenic plants turned yellow earlier with lower chlorophyll content. Transcriptome analysis identified a total of 1,392 differentially expressed genes (DEGs), involving 13 transcription factor families. Of which, 234 genes were related to phytohormone synthesis, metabolism and transduction. Pull-down assay and yeast one-hybrid assay confirmed that alfalfa zinc finger CCCH domain-containing protein 39 (MsC3H-39) could directly bind the upstream of MsSAG113 gene. In conclusion, the MsSAG113 gene plays a crucial role in plant leaf senescence, which provides an essential basis for further analysis on the regulatory network involving senescence-associated genes in alfalfa.